A Donor Age-Based and Graft Volume–Based Analysis for Living Donor Liver Transplantation in Elderly Recipients. Issue 7 (July 2017) - Imamura, Hajime; Hidaka, Masaaki; Soyama, Akihiko; Kitasato, Amane; Adachi, Tomohiko; Ono, Shinichiro; Natsuda, Koji; Hara, Takanobu; Kugiyama, Tota; Baimakhanov, Zhassulan; Okada, Satomi; Fujita, Fumihiko; et al.
Abstract : Background: Given the expected increase in the number of elderly recipients, details regarding how clinical factors influence the outcome in living donor liver transplantation (LDLT) for the elderly remain unclear. We examined the survival outcomes according to the results of donor age-based and graft volume–based analyses and assessed the impact of prognostic factors on the survival after LDLT for elderly recipients. Methods: The 198 adult recipients were classified into 2 groups: an elderly group (n = 70, E group; ≥ 60 years of age) and a younger group (n = 128, Y group; <60 years of age). We analyzed the prognostic factors for the survival in the E group and the survival rate for both groups at several follow-up points and conducted subgroup analyses in the E group by combining the donor age (≥50 vs <50 years) and graft weight (GW)/standard liver volume (SLV) (≥40% vs <40%). Results: Donor age (hazard ratio [HR], 2.17; P = 0.062) and GW/SLV (HR, 1.80; P = 0.23) tended to have a high HR in the E group. The overall patient survival rates at 1, 3, and 5 years were 78.3%, 73.0%, and 61.0% in the E group, and 82.0%, 75.1%, and 69.2% in the Y group, respectively ( P = 0.459). However, the outcomes tended to be worse in recipients of grafts from donors ≥50 years of age than in those with grafts from younger donors with GW/SLV < 40% ( P = 0.048). Conclusions: A worse outcome might be associated with aging of the donor, which leads to impairment of the graft function and liver regeneration. Both the graft volume and donor age should be considered when choosing grafts for LDLT in elderly patients.